Southern Pine Beetle, Dendroctonus frontalis Zimmermann (Insecta: Coleoptera: Scolytidae) - James R. Meeker; Wayne N. Dixon; John L. Foltz; Thomas R. Fasulo (EDIS)
The southern pine beetle (SPB), Dendroctonus frontalis Zimmermann, is the most destructive insect pest of pine in the southern United States. A recent historical review estimated that SPB caused $900 million of damage to pine forests from 1960 through 1990 (Price et a1. 1992). This aggressive tree killer is a native insect that lives predominantly in the inner bark of pine trees. Trees attacked by SPB often exhibit hundreds of resin masses (i.e., pitch tubes) on the outer tree bark. SPB feed on phloem tissue where they construct winding S-shaped or serpentine galleries. The galleries created by both the adult beetles and their offspring can effectively girdle a tree, causing its death. SPB also carry, and introduce into trees, blue-stain fungi. These fungi colonize xylem tissue and block water flow within the tree, also causing tree mortality (Thatcher and Conner 1985). Consequently, once SPB have successfully colonized a tree, the tree cannot survive, regardless of control measures. his document is EENY-176 (originally published as DPI Entomology Circular 369), one of the Featured Creatures series of the Entomology and Nematology Department, Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2000. Revised: March 2004.